Ruzpita (Azolla Pinnata Grass) As An Organic Fertilizer Of Nitrogen Binder (N2) In Increasing Plant Production Of Padi (Oryza Sativa) - Ilham Anggit Prayoga; Alvin Nugroho; Andri Abdi (JASc (Journal of Agribusiness Sciences), 2019)
Azolla is one type of algae plant that can be used as organic fertilizer, especially for rice cultivation. Azolla can be used as an organic fertilizer that is able to meet nutrient requirements, especially N for plants. Azolla's ability to provide N for plants is because in Azolla there are Cyanobacteria which then both do symbiotic mutualism. The second symbiosis is then called Anabaena azollae. Anabaena azollae can fix N2 freely in the air so that it can contribute to the need for N for plants in the soil.